Migraine Modulation and Debut after Percutaneous Atrial Septal Defect Closure: A Review - Leger, Charles Stevens; DeSouza, Joseph F. X. (Frontiers in Neurology, 2017)
Abstract INTRODUCTION: Change in migraine headache (MH) - pre-existing MH change or development of de novo MH - are known potential complications following percutaneous closure of atrial septal defect (ASD), but consensus on a causal trigger remains elusive. OBJECTIVES: To expose potential MH triggers linked, mainly by timing and occurrence, to the emergence of de novo MH or change in pre-existing MH subsequent to percutaneous ASD closure (pASDC). METHODS: The literature was systematically searched for studies available in English reporting MH status after pASDC published between Jan 1, 1990 and November 15, 2015. We determined the number and percentage of patients experiencing MH status change within 7-days post procedure and the cumulative total by final follow-up (Mdn =12 months). RESULTS: Twenty-five studies met the inclusion criteria, which accounted for a total of 1646 pASDC patients. Pre-procedure MH prevalence was 8% (126/1646). Change in pre-existing MH occurred in a total of 72% (91/126), 12% (11/91) within 7-days after pASDC; within follow-up MH improved in 14% (18/126), resolved in 37% (47/126), but persisted in 63% (79/126). De novo MH incidence ranged between 10% (153/1520) and 18.3% (153/836); 34% incipience (52/153) was within 7-days of pASDC; females accounted for 80% (63/79) of gender differentiated cases; of type distinguished cases, 42% (51/122) were MH without aura (MO) and 58% (71/122) were MH with aura (MA); MH improved in 10% (16/153), resolved in 24% (37/153) but persisted beyond final follow-up in 76% (116/153). Antiplatelet agents were effective modulators of MH in 44% (11/25) studies. Possible adverse MH-predisposing traits were scarce: larger ASD size reported in ~ 2% (39/1646) of patients experiencing de novo MH or pre-existing MH exacerbation; short aortic rim reported in 3 de novo MH patients; allergic response to occluder nickel alloy in 4 patients with MH status change from baseline (de novo or pre-existing MH change not specified). INTERPRETATION: Early intensification of MH status change but later amelioration (virtually paralleling stages of endothelialization), relatively high efficacy of antiplatelet agents, and the emergence of MA as the dominant de novo MH type, favour proinflammatory triggers of MH status change after pASDC.